2017
DOI: 10.23736/s0022-4707.16.06143-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of static and dynamic stretching on jump performance after 15 min of reconditioning shooting phase in basketball players

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Muscular power was assessed predominantly using jump tests, with 80 (58%) of the 137 studies in this review employing 18 different jump tests (Table 4 of the ESM). The three most frequent jump tests adopted across studies were the CMJ (43 studies, 54% of studies assessing muscular power) [ 14 , 16 , 27 , 48 , 51 , 54 , 55 , 58 , 61 75 77 – 96 ], VJ (27 studies, 34% of studies assessing muscular power) [ 3 , 14 , 28 , 39 , 56 , 59 , 62 , 66 , 82 , 90 – 92 , 96 – 100 , 102 – 111 ], and SJ (15 studies, 18% of studies assessing muscular power) [ 27 , 58 , 61 , 63 , 67 , 72 , 77 – 79 , 81 , 89 , 90 , 93 , 95 , 96 ]. Additional jump tests used across studies are reported in Table 4 of the ESM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscular power was assessed predominantly using jump tests, with 80 (58%) of the 137 studies in this review employing 18 different jump tests (Table 4 of the ESM). The three most frequent jump tests adopted across studies were the CMJ (43 studies, 54% of studies assessing muscular power) [ 14 , 16 , 27 , 48 , 51 , 54 , 55 , 58 , 61 75 77 – 96 ], VJ (27 studies, 34% of studies assessing muscular power) [ 3 , 14 , 28 , 39 , 56 , 59 , 62 , 66 , 82 , 90 – 92 , 96 – 100 , 102 – 111 ], and SJ (15 studies, 18% of studies assessing muscular power) [ 27 , 58 , 61 , 63 , 67 , 72 , 77 – 79 , 81 , 89 , 90 , 93 , 95 , 96 ]. Additional jump tests used across studies are reported in Table 4 of the ESM.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers and practitioners are encouraged to diligently consider the tests they select when assessing physical characteristics in players, as each test and testing methodology has an inherent level of accuracy and reproducibility [ 140 ]. For example, when considering the methodology of jumping tests, a range of technology with varying levels of accuracy have been used to assess jump height, including force platforms [ 16 , 61 , 71 , 110 ], three-dimensional cameras [ 110 ], contact mats [ 62 , 83 , 96 ], Vertec [ 107 ], and chalk marks on a wall [ 103 , 104 ]. The nuances associated with the various methodologies could influence results and need to be considered when comparing results between studies [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fletcher et al showed [ 53 ] that DS was able to significantly elevate muscle temperature and ultimately reverse longitudinal jump performance compared to SS. Furthermore, some scholars have found that the ability of DS to enhance subsequent explosive could be related to the preactivation of movement patterns [ 46 , 54 ]. Studies have shown that it might stimulate the muscle shuttle to increase muscle reflex activity, thus allowing the muscle to better complete active contractions based on the characteristics of the subsequent movement and ultimately inducing a postactivation potentiation effect (PAP) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fletcher et al showed 53 that DS was able to signi cantly elevate muscle temperature and ultimately reverse longitudinal jump height compared to SS. Furthermore, some scholars have found that the ability of DS to enhance subsequent explosive performance could be related to the preactivation of movement patterns 54,55 . Studies have shown that it might stimulate the muscle shuttle to increase muscle re ex activity, thus allowing the muscle to better complete active contractions based on the characteristics of the subsequent movement and ultimately inducing a postactivation potentiation effect (PAP) 56 .…”
Section: Dynamic Stretching Affects the Effectmentioning
confidence: 99%